Mechanisms and potential therapeutic molecular targets in blood–brain barrier disruption following subarachnoid hemorrhage: a review of early brain injury - Ouyang, Hao; Gu, Hua; Cai, Yong; Wang, Chenli (Frontiers in Neurology, 2025)
Subarachnoid hemorrhage (SAH) is a devastating stroke characterized by acute onset, severe symptoms, and a poor prognosis. A series of pathological changes occur within 72 h after SAH, leading to early brain injury (EBI). Blood–brain barrier (BBB) disruption is a key factor contributing to the EBI progression. When the BBB is compromised, detrimental substances and immune cells have the potential to infiltrate brain tissues, and a range of mechanisms contribute to the disruption of the BBB following SAH. This review provides a comprehensive overview of the current knowledge regarding the underlying mechanisms and potential therapeutic targets in BBB disruption during EBI following SAH. It focuses on the dysfunction of endothelial cells, tight junctions, astrocytes, and pericytes; the specific molecular targets for EBI after SAH; and new emerging treatments for BBB disruption in EBI after SAH.